FORTIFICATION OF DAIRY MILK WITH DOCOSAHEXAENOIC ACID (DH A) THROUGH FEED SUPPLEMENTATION OF DAIRY CATTLE FEED - A NEW HORIZON IN DAIRY INDUSTRY - I. Ahmad; U. E. Aiman; K. B. Marwat (Journal of Animal and Plant Sciences, 2012)
Docosahexaenoic acid (DHA) is an omega-3 fatty acid essential for structural development of the brain and eyes in the infants and maintenance of normal vision and neural functions in adults. DHA is also vital for the integrity of heart and vascular system, and is implicated in relieving inflammatory conditions and arthritis pain and in preventing cancer. Human body cannot synthesize DHA sufficiently, and most common source of DHA is marine food. Lowest breast-milk DHA values (0.06–0.14%) in nursing mothers found in Pakistan and inland areas of Canada have been attributed to a lack of dietary intake of marine food. In Canada, a novel approach of fortifying the dairy milk by supplementing the cattle feed with DHA-rich herring meal has been used to enhance the dietary intake of DHA in the country. In Pakistan a homegrown source of DHA is needed for supplementing cattle feed is needed to augment the low availability of marine food sources, and seems feasible to cultivate the marine red alga Crypthecodinium cohnii, which is a prolific producer of DHA and has been used as a non toxic pharmaceutical supplement. Crypthecodinium cohnii addition to duck feed has been shown to result in a significant increase in the DHA content of the fed animal. The current study deals with developing a sustainable mass culturing system for C. cohnii in Pakistan, using both bioreactors and open pond fields. The fortification of cattle feed is intended for both large scientifically managed “smart” dairy farms, and small to medium size family owned farms in different parts of the country. Our research is focused on developing protocols for custom designing the DHA enrichment of cattle feeds used in the area.
Keywords: Omega-3 fatty acid; docosahexaenoic acid deficiency; DHA; Crypthecodinium cohnii; milk fortification; customized cattle feed; dairy